Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1748302620942467
|View full text |Cite
|
Sign up to set email alerts
|

NSGA-II algorithm and application for multi-objective flexible workshop scheduling

Abstract: Based on the study of multi-objective flexible workshop scheduling problem and the learning of traditional genetic algorithm, a non-dominated sorting genetic algorithm is proposed to solve and optimize the scheduling model with the objective functions of processing cycle, advance/delay penalty and processing cost. In the process of optimization, non-dominated fast ranking operator and competition operator are used to select the descendant operator, which improves the computational efficiency and optimization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…As a stochastic procedure, metaheuristic optimization presents a powerful technique for computing near-optimal solutions to such problems (Elbeltagi et al 2005;Zhang et al 2006;Bozorg-Haddad et al 2017). Within metaheuristic techniques, genetic algorithms have been shown to be very efficient (Owais 2014) and have been utilized to solve challenging multiobjective optimization problems (Yusoff et al 2011;Rajkumar et al 2014;Yahui et al 2020). The nondominated sorting genetic algorithm (NSGA-II) is an example of such techniques where it has been employed to solve multiobjective schedule optimization-related problems (Vanucci et al 2012;Polat et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…As a stochastic procedure, metaheuristic optimization presents a powerful technique for computing near-optimal solutions to such problems (Elbeltagi et al 2005;Zhang et al 2006;Bozorg-Haddad et al 2017). Within metaheuristic techniques, genetic algorithms have been shown to be very efficient (Owais 2014) and have been utilized to solve challenging multiobjective optimization problems (Yusoff et al 2011;Rajkumar et al 2014;Yahui et al 2020). The nondominated sorting genetic algorithm (NSGA-II) is an example of such techniques where it has been employed to solve multiobjective schedule optimization-related problems (Vanucci et al 2012;Polat et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…NSGA-II is the standard metaheuristic for solving multi-objective optimization problems [29]. It has been applied to various search and optimization problems, such as scheduling problems [45], resource allocation problems [19], and optimal parameter selection problems [39]. The algorithm modifies the processes of mating and survival selection of individuals.…”
Section: Bilateral Filtermentioning
confidence: 99%
“…For example, Tang et al [9] proposed the use of a HTLBO algorithm, which has been shown to perform better than other traditional heuristic algorithms. Wang et al [10] proposed a non-dominated sorting genetic algorithm to solve the multi-objective flexible job-shop scheduling problem and optimize the scheduling model with periodicity. Other algorithms include Particle Swarm Optimization (PSO) and Artificial Bee Colony optimization (ABC).…”
Section: Introductionmentioning
confidence: 99%